A bandpass wavelet OFDM system for power line communications. Issue 11 (July 2020) - Pinto-Benel, Freddy A.; Cruz-Roldán, Fernando
Abstract: A bandpass wavelet OFDM system, based on the time-domain waveform signals described in the standard IEEE Std. 1901-2010 for broadband power line communications, is presented. Several important aspects of the bandpass physical layer are reviewed, focusing on the scheme of modulation. Furthermore, a viable receiver system that is compatible with the transmitter and that also includes an equalizer system, is proposed. This paper also derives theoretical expressions for different powers at the receiver side, corresponding to the desired signal, as well as to the intersymbol and the intercarrier interference, and the noise. With these expressions, the signal-to-interference plus noise ratio and the achievable data rate of wavelet OFDM for bandpass communications are calculated. Finally, several computer simulations complete this work, assuming different PLC scenarios.